(untitled) (Journal of Forensic Medicine & Toxicology, 2024)
Present article describes the pattern of aluminum phosphide poisoning observed retrospectively. Aluminum phosphide (ALP) is a widely used pesticide, notorious for preferred mean of suicide in India. Ongoing socioeconomic conditions and thus lifestyle led to psychological shift thatresulted in significant morbidity and mortality due to ALP poisoning. Demographic and forensic details of patients admitted in a year were systematically summarized, represented with tabular/ graphical mean and analyzed using appropriate statistical test.Significant cases of intensely poisoning in age group of 21-30 years were belonged to rural areas. Maximum cases got medical treatment 2-4 hours after poisoning. Cardiovascular (69.82%), gastrointestinal (68.96%), shock (36.65%), respiratory (14.65%), renal (10.34%) and central nervous system (03.44%) related clinical manifestations were observed. Tachycardia (65.51%), ST elevation (29.31%), atrial fibrillation (AF) (08.62%), ST depression (02.58%) and atrioventricular (AV) block (00.86%) were recorded ECG abnormalities. Deranged LFT (liver function test), ABG (arterial blood gas), CPK-NAC (creatine phosphokinase n-acetyl) and KFT (kidney function test) were observed in 37.89%, 20.09%, 15.98% and 12.78% lab investigations. Gastric lavage was supplemented with magnesium sulphate (91.37%), levocarnitine (68.10%), inotropes& vasopressor support (43.10%), hydrocortisone (42.24%), Sodium Bicarbonate (41.37%) and activated charcoal (06.89%) for poison elimination. 57.75% victims got expired while 26.72% victims improved. 13.81% cases relieved after medical advice and 01.72% cases were referred to higher centers. Socioeconomic wellbeing, earliest hospitalization and appropriate detoxification with intensive care are advisable to overcome such mishappenings.